A rare variant of uterine leiomyoma-lipoleiomyoma - Goyal, Lipsy; Phool, Divya; Jain, Chanchal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Lipoleiomyoma is a benign variant of uterine leiomyoma characterized by admixture of fat cells and smooth muscle cells. This entity can coexist with other malignancies in uterus, ovaries and fallopian tubes. Lipoleiomyoma is typically found in post-menopausal women with incidence of 0.03-0.20%. The 58 years old postmenopausal women presented to gynaecology outpatient department (OPD) with complaints of chronic lower abdominal pain. Her clinical examination and blood investigations were normal but her imaging showed a large heterogenous solid mass at uterine fundus. She underwent TAH and BSO. Diagnosis of lipoleiomyoma was confirmed on histopathological examination. Left ovary showed serous cystadenomatous cystic lesion and left fallopian paratubal cyst. Lipoleiomyoma is rare entity with excellent prognosis when asymptomatic so its awareness is important to avoid unnecessary surgeries.